The Visual Rehabilitation of Bilateral Posterior Lens Luxation In Children: A Case Report - Yunneke Renna Xaverina; Anny Sulistiyowati; Lely Retno Wulandari (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Dislocated lens can be subluxated (partial) or luxated (complete), which can cause visual impairment in children. Conservative visual rehabilitation is an option for luxated lens treatment. Purpose: This study reports the possibility for visual rehabilitation of bilateral of bilateral luxated lens in children. Case Report: A 3-year-old boy came to the outpatient clinic of Dr. Saiful Anwar General Hospital with complaints of blurred vision on both eyes. The child would always bring objects close to his eyes since the past year. There was no history of ocular injury nor development disorder. Uncorrected visual acuities with LEA symbol on both right and left eyes were 6/114. The best-corrected visual acuity (BCVA) of the right eye was 6/45 and left eye was 6/9 with both S+11.00. Iridodonesis and aphakic lenses were found during slit-lamp examination of both eyes. The intraocular pressures were 14.2 mmHg on the right eye and 17.3 mmHg on the left eye. The lenses were seen in the vitreous cavities during funduscopy and ultrasonography examination. After 1 month of using spectacles, the BCVA of the right eye was 6/18 and that of the left eye was 6/18 with the binocular BCVA was 6/15. Lensectomy with pars plana vitrectomy was planned to prevent complication. Conclusion: Conservative visual rehabilitation is important to prevent amblyopia in children with luxated lenses and surgical treatment is needed to prevent complication. In this patient, aphakic spectacles were given for visual rehabilitation pending operative treatment.